Transport factor in defining regional boundaries - I. V. Anokhov (Вестник университета)
The purpose of the article is to study the economic region as a set of reproduction circuits closely intertwined. The theoretical underpinning of the research is the concept of “Universal organisational science” introduced by Alexander A. Bogdanov. The author of this article proposes to analyze economic regions on the basis of this concept, that is to say indirectly, through the assessment of the movement of goods transport along reproduction circuits. It is pointed out that transport conjoins disparate industries into a single reproduction chain, thus acting as the main region-building factor. In terms of transport links, economic regions are classified by the author as follows: economically isolated regions, natural specialisation regions, technological specialisation regions, and emission centers. It is identified that at the latter stage of the establishment of boundaries of an economic region, the key limiting factor is the amount of transport costs and the purchase price of the transported product. The proposed classification is applied to the analysis of the economy of the Russian Federation. It is stated that road transport is the main region-building factor of the country.